Arthroscopic rotator cuff repair: single-row vs. double-row - clinical results after one to four years - Luís Filipe Senna; Max Rogério Freitas Ramos; Ricardo Folador Bergamaschi (Revista Brasileira de Ortopedia)
ABSTRACT Objective: Evaluate and compare the results of single-row (SR) vs. double-row (DR) arthroscopic rotator cuff repair. Methods: From December 2009 to May 2013, 115 arthroscopic rotator cuff repairs were performed using suture anchors. After applying the exclusion criteria, there were 75 patients (79 shoulders) to be evaluated, retrospectively, of whom 53 (56 shoulders) attended re-evaluation. The patients were divided into two groups: SR with 29 shoulders, and DR) with 27 shoulders. The scoring systems for clinical evaluation were those of the University of California at Los Angeles (UCLA) and the American Shoulder and Elbow Surgeons (ASES). Results: The mean follow-up period in the SR group was 37.8 months vs. 41.0 months in the DR group. The average UCLA score was 30.8 in the SR group vs. 32.6 in the DR group. This difference was not statistically significant (p > 0.05). The averages measured by the ASES score also showed no significant difference - 82.3 and 88.8 in the SR and DR groups, respectively. Conclusion: No statistically significant difference was found between SR and DR arthroscopic rotator cuff repair performed by a single surgeon in the comparative analysis of UCLA and ASES scores.